Tuberculous abdominal aortic pseudoaneurysm with renal and vertebral tuberculosis: a case and literature review - Chao Zhang; Bing Chen; Yongquan Gu; Tao Luo; Shengjia Yang; Weitao Liang; Zhonggao Wang (Journal of Infection in Developing Countries)
Tuberculous pseudoaneurysm of the aorta is rare and exposes patients to a very high risk of unpredictable rupture. To our best knowledge, only 32 cases have been reported related to all arterial systems from 1993 to 2013 in the literature. We report a 44-year-old male who presented with an aortic pseudoaneurysm and tuberculosis of the kidney and vertebrae. He underwent endovascular repair and antibiotic therapy for tuberculosis, combined with a bare stent implanted to seal endoleaks after endograft stenting. The postoperative course was uneventful and the patient recovered and lived well afterwards. Epidemiology, pathogenesis, presentation, management, and mortality of this entity were reviewed and discussed.